Carbohydrate supplementation during a simulated 10-km open water swimming race: effects on physiological, perceptual parameters and performance - Baldassarre, R.; Ieno, C.; Bonifazi, M.; Di Castro, A.; Gianfelici, A.; Piacentini, M. F. (European Journal of Sport Science, 2022)
The aim of the present study was to test the effect of carbohydrate ingestion, simulating a 10-km open water race competition on energy cost (Csw), perceived exertion (RPE), heart rate (HR), stroke rate (SR) and performance. We hypothesized that carbohydrate ingestion would reduce Csw and RPE in elite open water swimmers (OW-swimmers) and improve performance. Eight elite OW-swimmers swam for 3 × 30 min with 20-s of interval necessary to collect data in the swimming flume at a pre-set pace corresponding to their 10-km race pace, followed by a time to exhaustion test (TTE) at 100% of the peak oxygen uptake (VO2peak). During the set, OW-swimmers ingested 45-g of carbohydrates (CHO) in 550-mL of water (8% solution) during each of the two intervals or a placebo solution (PLA). HR, RPE, VO2 and SR were measured. Shapiro-Wilk test was used to verify the normal distribution of data. Two-way repeated measures ANOVA and t-test was performed (p < 0.05). A significant difference emerged in TTE between the trials (169.00 ± 91.06 s in CHO; 102.31 ± 57.47 s in PLA). HR, RPE and SR increased during the TTE but did not differ between trials. Csw did not show a significant main effect between the two conditions and in time course in both conditions. CHO ingestion significantly increased TTE at 100% of VO2peak after 90-min of swimming at 10-km race pace. These findings indicate that CHO intake during a 10-km open water swimming competition should have a beneficial impact on performance in the final part of the race.